Peningkatan Kemampuan Analisis pada Mata Pelajaran Pendidikan Pancasila dan Kewarganegaraan dengan Menerapkan Model Pembelajaran Kooperatif Picture and Picture - Tiurma Simatupang (Departement of Mathematics Education, 2021)
This study aims to improve analytical skills in Pancasila and citizenship education subjects by applying the picture and picture cooperative learning model. The subjects of this study were 33 students of class 1-A. This research was conducted at SDN Wonokusumo VII/46 Surabaya with an action research mechanism consisting of two cycles of action. Based on the results of data analysis and discussion, it can be concluded that the application of the picture and picture cooperative learning model can improve the ability to analyze and improve student achievement in Class III-B SDN Wonokusumo VII/46 Surabaya City. This can be seen from the increase in the ability to analyze students in improving their learning outcomes. The effectiveness of the application of the picture and picture cooperative learning model in improving student achievement in Class III-B SDN Wonokusumo VII/46 is shown through an increase in the average post-test score, an increase in the percentage of classical completeness and an increase in the value of observation on students' analytical skills. The average post-test score in cycle I was 74.5 and cycle II was 78.4. Classical completeness in cycle I 76% and cycle II 94%. The average value of the observation on the students' ability to analyze in cycle I was 79.6 and cycle II was 82.0.